A Further Phase of Archaeological Investigations at Swalwell Ironworks, Tyne and Wear. (2nd January 2022) - Lotherington, Rupert; Miller, Ian; McDonnell, Gerry
ABSTRACT: Archaeological Research Services Ltd carried out an archaeological excavation of part of the 18th-century Swalwell Ironworks near Gateshead during the summer of 2016 in advance of a redevelopment of the site by Lidl UK. This explored a part of the ironworks immediately to the west of a previous excavation directed by Pre-Construct Archaeology in 2005, and has contributed significant detail to the overall record of this important ironworking site. In particular, the excavation in 2016 uncovered well-preserved structural remains deriving from the early 18th-century development of the site, including the western portion of Ambrose Crowley's Grand Warehouse and its basement wharf, an anchor shop, a series of ancillary workshops and a curving water channel that formed the northern boundary of the archaeological site. Amongst the remains deriving from the later use of the works was part of a mid-19th-century crucible furnace. The excavation has also indicated that well-preserved archaeological remains are likely to exist beyond the western and southern limits of the excavated area.